Colima and Manila: Two cities linked by history - Paulina Machuca Chávez (Portes: Revista mexicana de estudios sobre la Cuenca del Pacífico, 2012)
During more than two centuries, Colima and Manila had a close relationship, as a result of the transpacific voyages held by the Manila Galleon. In its voyage towards Acapulco, this ship stopped first in the port of Salagua (Manzanillo, Colima), in order to get food supply and to send the viceroy of the New Spain an official report about the status of the merchandise. In this context, many Asian people (known as "indios chinos" in the New Spain) landed in Colima and established in the haciendas de palmas (Machuca, 2009a), very familiar to them because palm trees are native of Asia. Philippine people taught Spaniards and American indians how to use the coconut (Cocos nucifera L.) to make beverages, dishes and tools, as well as to build houses known as “palapas”. This heritage survives nowadays, and it takes part in the Colima everyday life. I present ten evidences of the close relationship that existed between these two cities from the second half of the Sixteenth century up to the Independence phase. I consider that this information will be useful to promote a "sister cities"municipal project between Colima and Manila.